2013
DOI: 10.1016/j.jconrel.2013.07.024
|View full text |Cite
|
Sign up to set email alerts
|

The effects of lipoplex formulation variables on the protein corona and comparisons with in vitro transfection efficiency

Abstract: The use of lipoplexes for the intracellular delivery of nucleic acids typically involves the optimization of several parameters that are known to affect delivery. Researchers commonly vary charge ratio, and often incorporate different amounts of helper lipids (e.g., cholesterol) to optimize formulations for transfection in cell culture and in vivo. The results of such experiments are often interpreted in the context of nuclease resistance and cell association, but effects on the protein corona are usually not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 48 publications
(88 reference statements)
0
31
0
Order By: Relevance
“…In fact, several studies have reported that PEGylation increases protein adsorption, suggesting that the binding of specific proteins involved in clearance might be preferentially inhibited by PEG [13,14]. Alternatively, it has been suggested that PEG may preferentially bind proteins that function as “dysopsonins”, i.e., proteins that prevent opsonization [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, several studies have reported that PEGylation increases protein adsorption, suggesting that the binding of specific proteins involved in clearance might be preferentially inhibited by PEG [13,14]. Alternatively, it has been suggested that PEG may preferentially bind proteins that function as “dysopsonins”, i.e., proteins that prevent opsonization [11].…”
mentioning
confidence: 99%
“…Consistent with the studies cited above, Figure 1 shows data from our laboratory indicating that PEGylation of lipoplexes dramatically increases the extent of serum protein binding compared to non-pegylated lipoplexes. Furthermore, our recent publication also demonstrates that small proteins (potentially protein fragments) bind to PEGylated nanoparticles that are not adsorbed to particles lacking PEG [14]. While it has been shown that the density/conformation of PEG molecules on the surface affects protein binding [6,11,15], studies demonstrating enhanced serum protein binding and the adsorption of specific proteins after PEGylation raise significant questions about the ability of PEG to prevent/reduce interactions with serum proteins.…”
mentioning
confidence: 99%
“…In addition to the lipoplex formulation described above, mice were treated with phosphate buffered saline (negative control), lipoplexes formulated with 5% DSPE-PEG2000 (Avanti), CpG-containing plasmid (Valentis, Inc.), 1,2-dioleoyl-3-trimethylammonium-propane (DOTAP; Avanti) instead of sphingosine, or Lipofectamine 2000 (Invitrogen, Carlsbad, CA) as previously described [19, 20, 22, 25]. In these studies, a single mouse was treated with each formulation as described above, and blood was collected in Eppendorf tubes 2 h after the second injection of lipoplexes.…”
Section: Methodsmentioning
confidence: 99%
“…Besides the changes in the composition of the EV itself, the presence or absence of serum proteins will likely also influence the protein corona surrounding the EVs . It is well documented that this corona strongly influences the extra-and intracellular (transfection) behavior of synthetic nanoparticles, including liposomes [56,57]. Given the analogy between EVs and liposomes [58] it is conceivable that a protein corona will also impact the EV interactome and hence biological function.…”
Section: )mentioning
confidence: 99%